Attitudes and their Measurement through Attitude Scale based upon the “Likert” Method (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Criticially, Analytically and scientifically contraction of an Attitude scale requires : careful selection or topic, plot study to establish reliability and item anslysis for internal consistency for the scale’s items. Thus throughout competition of the above said `Likert Attitude Scale’ Process brings an effective attitude scale to measure the attitude scale to measure the attitude.No one is born with any Attitude. it is an acquired tendency, which prepares a person to behave favorably or unfavorably towards a specific object or class of subjects to the conditions prevailing.The notion Attitude was initially introduced into Experimental Psychology by german Psychologist to designate some factor conditioned by past experience like readiness to act in a given way.The affective bio-product of the individual's experience, have their basis in his/her urges, requirement and environment influences by which he or she is surrounded. In other words be can say that Attitude arise from personal desire and group stimulation.Attitude act as causes as well as results of behavior. They are personal and are associated with the feeling tones connected with the individual's experiences. They represent the way he feels as he thinks, talks or act in any situation.According to Charles E. Skinner; "Attitudes are ideas with emotional contents, important beliefs, prejudices, biases, predispositions, appreciations and states of readiness or set. Edward" quoted about……………., we undevourable attitude are obstacles to learning. The removal or change of these unfavourable attitude should bring about an increase in learning steps, should be taken to strength the favorable attitude and to remove or change the unfavourable attitude.